Redirecting education library and information science for the information society: Some reflections - Barber, Elsa (2004)
Throughout history, the development of agriculture took centuries to take shape in expanded and become known in most cultures. During the past 200 years, part of mankind has been dominated by industrial activity. While the world struggles to participate in the RevolutionIndustrial, some nations are going through a stage that transforms everything so extraordinarily fast. This is what is called "information society". There can be no doubt that society is entering a new era in which every aspect of people's lives are characterized by the applications of Information Technology and Communication (ICT). Presented in this new environment, some changes that should be asked in the training of information professionals.